2020
DOI: 10.21608/jpp.2020.122666
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Productivity of Two Cabbage Cultivars Grown in Sandy Soil as Affected by Foliar Spray with Npk Fertilizer and Amino Acids

Abstract: The present work was carried out at Private Farm (The Experimental Farm of Sand Valley Company) at Ismailia, Ismailia Governorate, Egypt during 2017 / 2018 and 2018 / 2019 seasons to study the effect of foliar spray with NPK (15-15-15) fertilizer at 1 or 2 ml/l and amino acids at 1.5 or 3 ml/l on two cabbage cultivars (OS Cross and Landini ) grown under sandy soil conditions. The interaction between OS Cross cultivar and spraying with amino acids at 3 ml/l and NPK (15-15-15) fertilizer at 2 ml / l increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In addition, a field experiment was conducted to evaluate the growth, productivity, and economics of cabbage in the grid zone as influenced by different levels of zinc and sulfur reported that growth parameters such as plant height, plant spread, number of leaves per plant at all crop growth stages, yield attributing characters, length and diameter of head and weight per head, cabbage yield per hectare net return, and benefit cost ratio increased with increasing levels of sulfur from 20 to 80 kg/ha and zinc from 2 to 8 kg/ha and the crop responded only up to 60 kg S/ ha and 6 kg Zn/ha [ 61 , 62 ]. During a 2017 experiment in Ghana's Kintampo North Municipality, evaluating cabbage response to various soil amendments from August to November, poultry manure matched NPK (15-15-15) and outperformed other treatments across all measured parameters, while cow dung and goat manure also exhibited promising results [ 63 , 64 ]. Likewise, a field experiment conducted to determine the optimum combination of FYM and biofertilizers for improving the growth, yield, and quality attributes of Chinese cabbage under high-altitude rain-fed climatic conditions reported that among the treatments studied, the highest plant height (33.33 cm), number of wrapper leaves/plant (18.00), plant spread/plant (111.66 cm), head weight/plant (553.33 g), yield/plot (15.49 kg), yield/ha 34.42 tons, moisture content 98.00%, and vitamin C 28 mg/100 g were observed with the application of FYM at 25 tons/ha along with an azotobactor and phosphate-solubilizing bacteria [ 65 ].…”
Section: The Effect Of Nitrogen On the Cabbage Yieldmentioning
confidence: 99%
“…In addition, a field experiment was conducted to evaluate the growth, productivity, and economics of cabbage in the grid zone as influenced by different levels of zinc and sulfur reported that growth parameters such as plant height, plant spread, number of leaves per plant at all crop growth stages, yield attributing characters, length and diameter of head and weight per head, cabbage yield per hectare net return, and benefit cost ratio increased with increasing levels of sulfur from 20 to 80 kg/ha and zinc from 2 to 8 kg/ha and the crop responded only up to 60 kg S/ ha and 6 kg Zn/ha [ 61 , 62 ]. During a 2017 experiment in Ghana's Kintampo North Municipality, evaluating cabbage response to various soil amendments from August to November, poultry manure matched NPK (15-15-15) and outperformed other treatments across all measured parameters, while cow dung and goat manure also exhibited promising results [ 63 , 64 ]. Likewise, a field experiment conducted to determine the optimum combination of FYM and biofertilizers for improving the growth, yield, and quality attributes of Chinese cabbage under high-altitude rain-fed climatic conditions reported that among the treatments studied, the highest plant height (33.33 cm), number of wrapper leaves/plant (18.00), plant spread/plant (111.66 cm), head weight/plant (553.33 g), yield/plot (15.49 kg), yield/ha 34.42 tons, moisture content 98.00%, and vitamin C 28 mg/100 g were observed with the application of FYM at 25 tons/ha along with an azotobactor and phosphate-solubilizing bacteria [ 65 ].…”
Section: The Effect Of Nitrogen On the Cabbage Yieldmentioning
confidence: 99%